Decades of leopard coexistence in the Himalayas driven by ecological dynamics, not climate change - Paras Bikram Singh; Pradip Saud; Prakash Chandra Aryal; Pawan Rai; Jeff R. Muntifering; Huijian Hu; Ajay Karki; Yiming Hu; Kumar P. Mainali (Global Ecology and Conservation)
The interaction between two predators in overlapping habitats with distinct habitat requirements poses critical challenges for conservation and management strategies. This study explores the ecological dynamics and coexistence of common leopards (Panthera pardus) and snow leopards (Panthera uncia) in the Himalayan regions, explicitly focusing on their spatial and temporal distribution as well as factors influencing their habitat overlap. Utilizing historical accounts dating back to the 1950s and our winter sighting data from trail cameras from 2016 to 2023 in the trans-Himalayan part of Annapurna Conservation Area of Nepal (3100–4696 m), we provide substantial evidence of the common leopard’s established residency at high altitudes traditionally associated with snow leopards. This challenges the notion that the co-occurrence of these species is a recent phenomenon attributable to climate change. Instead, our findings suggest a long-term adaptation of common leopards to high-altitude environments, demonstrated by their ability to survive and breed in cold temperatures as low as −18°C. We show that the likelihood of co-occurrence of the two leopard species increases with proximity to open forest canopy, farmland and greater distances from snowline. In contrast, steep terrain negatively impacted the likelihood of co-occurrence, highlighting the snow leopard’s specialized adaptations to rugged landscapes. Our analysis reveals a considerable overlap between common and snow leopards in sub-alpine mixed forest and alpine scrub. This overlap extends to dietary habits along the altitudinal range, with both species preying on similar wild and domestic animals, highlighting the potential for interspecies competition, especially during the winter months when prey availability decreases. Understanding the ecological dynamics is crucial for conserving both species, providing insights into their adaptation to environmental changes and informing necessary measures for their continued coexistence in the higher Himalayas.